The Effectiveness of the Performance of the Directorate of Vital Object Security of the West Sumatra Regional Police on the Security Level of the Padang-Sicincin Toll Road Construction - Yossa Indra Kurnia; Otong Rosadi (Master of Law Program, Ekasakti University, 2025)
This research is a legal research with descriptive analytical specifications. The performance of the Directorate of Vital Object Security of the West Sumatra Regional Police in securing the construction of the Padang-Sicincin toll road is to maintain the safety of vital objects around the toll road and ensure the safety of workers and construction facilities so that the construction process is not disrupted. Conducting regular escorts at several conflict-prone points, especially in areas that reject toll road traffic. Crime prevention in the project area. Obstacles in the Performance of the Directorate of Vital Object Security of the West Sumatra Regional Police in securing the construction of the Padang-Sicincin toll road include limited personnel with special competencies to handle complex disturbances, lack of supporting facilities, such as modern communication equipment and patrol vehicles. Lack of coordination between the police and related institutions. Unclear procedures in handling conflicts. The effectiveness of the performance of the Directorate of Vital Object Security of the West Sumatra Regional Police on the level of security of the construction of the Padang-Sicincin Toll Road has been effective as seen from the success of placing personnel to carry out routine patrols and supervision throughout the project. Success anticipates social conflicts, crime, and environmental protests. Successful physical security, solid coordination.